Frequency of Postnatal Depression among Patients in the Obstetrics and Gynaecology Department at a Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: To identify the percentage of postnatal depression and risk factors related to the condition among female patients.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology at Lahore Medical Dental College/Ghurki Trust & Teaching Hospital, Lahore from 28th July 2021 to 27th January 2022.Methods: Three hundred and sixty-nine postpartum women within six weeks of delivery, using the Edinburgh Postnatal Depression Scale to identify depressive symptoms were enrolled. An Edinburgh Postnatal Depression Scale score of 10 or higher indicated postnatal depression.Results: Mean age of patients was 30.60±4.34 years. Postnatal depression prevalence of 3.25% and mean Edinburgh Postnatal Depression Scale score was 6.78±4.33. Notably, 5.88% of mothers with male infants experienced postnatal depression compared to 1.39% with female infants (p = 0.017). Additionally, postnatal depression was frequent in cesarean section patients (5.88% vs. 1.01%, p = 0.009) and among those without social (6.67% vs 0.91%, p = 0.002) and partner support (4.40% without vs. 0% with, p=0.037). Unintended pregnancies had a higher association with postnatal depression (8.33% vs. 1.15%, p=0.0004), and those earning above 40,000 had increased depression rates (9.41%, p=0.001).Conclusion: There is a need for mental health screening and support services to mitigate the adverse effects on maternal and child well-being.